Loss to Followup in HIV-Infected Patients from Asia-Pacific Region: Results from TAHOD - Jialun Zhou; Junko Tanuma; Romanee Chaiwarith; Christopher K. C. Lee; Matthew G. Law; Nagalingeswaran Kumarasamy; Praphan Phanuphak; Yi-Ming A. Chen; Sasisopin Kiertiburanakul; Fujie Zhang; Saphonn Vonthanak; Rossana Ditangco; et al. (AIDS Research and Treatment)
This study examined characteristics of HIV-infected patients in the TREAT Asia HIV Observational Database who were lost to follow-up (LTFU) from treatment and care. Time from last clinic visit to 31 March 2009 was analysed to determine the interval that best classified LTFU. Patients defined as LTFU were then categorised into permanently LTFU (never returned) and temporary LTFU (re-entered later), and these groups compared. A total of 3626 patients were included (71% male). No clinic visits for 180 days was the best-performing LTFU definition (sensitivity 90.6%, specificity 92.3%). During 7697 person-years of follow-up, 1648 episodes of LFTU were recorded (21.4 per 100-person-years). Patients LFTU were younger (P=0.002), had HIV viral load ≥500 copies/mL or missing (P=0.021), had shorter history of HIV infection (P=0.048), and received no, single- or double-antiretroviral therapy, or a triple-drug regimen containing a protease inhibitor (P<0.001). 48% of patients LTFU never returned. These patients were more likely to have low or missing haemoglobin (P<0.001), missing recent HIV viral load (P<0.001), negative hepatitis C test (P=0.025), and previous temporary LTFU episodes (P<0.001). Our analyses suggest that patients not seen at a clinic for 180 days are at high risk of permanent LTFU, and should be aggressively traced.